A dynamic scheduling method for spatial layout planning - Bo Li; Zhi-Yan Zhao; Gang Li (2005 International Conference on Machine Learning and Cybernetics, 2005)
A dynamic scheduling approach for the spatial layout planning for block assembly in shipbuilding industry is proposed in this paper. Within a period of planning horizon, the whole procedure of the scheduling problem is composed of the pre-scheduling algorithm and the spatial planning by genetic algorithm (GA). The first part generates the initial set of blocks with respect to every working space by considering spatial constraints, due time of blocks and workload balance among the working space. In the spatial planning algorithm, GA is proposed to further realize the spatial layout of the initial set of blocks obtained in the pre-scheduling algorithm at a period in a working space. Because several locatable strategies such as rotation mechanism, edging strategy, rearrangement strategy have been designed to realize in the genetic operations, the feasible locatable point set can be found by GA. Finally, a simulation example is examined to show the validity of the proposed hybrid approach.